OPRM1 rs1799971, COMT rs4680, and FAAH rs324420 genes interact with placebo procedures to induce hypoalgesia. Issue 8 (August 2019) - Colloca, Luana; Wang, Yang; Martinez, Pedro E.; Chang, Yen-Pei C.; Ryan, Kathleen A.; Hodgkinson, Colin; Goldman, David; Dorsey, Susan G.
Abstract : Abstract: Genetics studies on the placebo hypoalgesic effect highlight a promising link between single nucleotide polymorphisms (SNPs) in the dopamine, opioid, and endocannabinoid genes and placebo hypoalgesia. However, epistasis and replication studies are missing. In this study, we expanded on previous findings related to the 3 SNPs in the opioid receptor mu subunit ( OPRM1 rs1799971), catechol-O-methyltransferase ( COMT rs4680), and fatty acid amide hydrolase ( FAAH rs324420) genes associated with placebo hypoalgesia and tested the effect of a 3-way interaction on placebo hypoalgesia. Using 2 well-established placebo procedures (verbal suggestion and learning paradigm), we induced significant placebo hypoalgesic effects in 160 healthy participants. We found that individuals with OPRM1 AA combined with FAAH Pro/Pro and those carrying COMT met/met together with FAAH Pro/Pro showed significant placebo effects. Participants with COMT met/val alleles showed significant placebo effects independently of OPRM1 and FAAH allele combinations. Finally, the model that included the placebo procedure and genotypes predicted placebo responsiveness with a higher accuracy (area under the curve, AUC = 0.773) as compared to the SNPs alone indicating that genetic variants can only partially explain the placebo responder status. Our results suggest that the endogenous mu-opioid system with a larger activation in response to pain in the met/val allele carriers as well as the synergism between endogenous mu-opioid system and cannabinoids might play the most relevant role in driving hypoalgesic responses. Future epistasis studies with larger sample sizes will help us to fully understand the complexity of placebo effects and explain the mechanisms that underlie placebo responsiveness. Abstract : Supplemental Digital Content is Available in the Text.Genetic variants in OPRM1, COMT, and FAAH along with the placebo procedure provide a robust estimation of likelihood to respond to placebos.